2006
DOI: 10.1016/j.ijid.2005.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen-induced multiple organ dysfunction in a toxin-concentration-controlled and sequential parameter-monitored swine sepsis model

Abstract: The superantigen TSST-1 plays an important role in the pathogenesis of Gram-positive bacterial sepsis by inducing multiple organ dysfunction. Thus, this model provides the first tool to allow the simultaneous examination of the serum toxin levels and other organ parameters in a time-course manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, these animals are too small for the monitoring of several physiological parameters, and tox- in concentrations in the circulating blood cannot be controlled and maintained at clinical levels. To overcome these problems, we have developed a sepsis model in swine that is toxin concentration controlled and with which a Swan-Ganz catheter can be used sepsis model in swine [14] ; in addition, this model is not lethal. Laboratory animals are intrinsically resistant to the toxicity of SAg and require far higher doses of SAg than do humans to induce shock; for this reason, prior sensitization with D -galactosamine or co-administration with LPS are used to induce lethality in low-dose, SAg-administration animal models [4,8] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, these animals are too small for the monitoring of several physiological parameters, and tox- in concentrations in the circulating blood cannot be controlled and maintained at clinical levels. To overcome these problems, we have developed a sepsis model in swine that is toxin concentration controlled and with which a Swan-Ganz catheter can be used sepsis model in swine [14] ; in addition, this model is not lethal. Laboratory animals are intrinsically resistant to the toxicity of SAg and require far higher doses of SAg than do humans to induce shock; for this reason, prior sensitization with D -galactosamine or co-administration with LPS are used to induce lethality in low-dose, SAg-administration animal models [4,8] .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of these changes, Qs/Qt and PaO 2 were signifi cantly improved by SAAD treatment ( fi g. 2 ). We previously reported that TSST-1-induced infi ltration of WBC into the lung is one of the causes of respiratory failure, which is measured as the correlation between the decrease in WBC counts and increase in PVR [14] . In this study, a statistically signifi cant correlation was observed between the decrease in the WBC count and increase in the PVR, which indicates the infi ltration of WBC into the lung in individual animals for the entire 6-hour observation period in both the SAAD-treated and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations